(untitled) (Research, Society and Development, 2022)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis, whose clinical symptomatology depends on the balance between the conditioning factors of the tuberculous lesion. In the Brazilian prison system, these conditions change due to the precarious situations in which people deprived of liberty find themselves, facilitating their contagion and constituting a relevant public health problem. This study is a quantitative, retrospective epidemiological study with descriptive approach, which aims to describe the epidemiological profile of tuberculosis in people deprived of liberty in Brazil between 2012 and 2019. The data were obtained from Sinan, available for consultation in the DATASUS database. According to the research, there was an increase in the number of tuberculosis cases reported in the LPP when compared to the numbers between 2012 and 2019, being, in most cases, male individuals, aged between 20-29 years, with mixed race/color and with the prevalent diagnosis of pulmonary-type TB. Thus, there is a great need for more effective TB control strategies in penitentiated women in Brazil, which promote both the comprehensive care of these patients and the prevention, promotion and rehabilitation of health.